Generation of a mouse line harboring a bi‐transgene expressing luciferase and tamoxifen‐activatable creERT2 recombinase in cartilage. Issue 2 (27th December 2013) - Cascio, Leandro Lo; Liu, Ke; Nakamura, Hiro; Chu, Grace; Lim, Ngee Han; Chanalaris, Anastasios; Saklatvala, Jeremy; Nagase, Hideaki; Bou‐Gharios, George
Summary We have used an aggrecan gene enhancer to generate a transgenic murine line (Acan‐CreER‐Ires‐Luc) expressing firefly luciferase and tamoxifen activatable Cre recombinase (Cre‐ERT2). The expression and efficiency of the inducible Cre recombinase activity were tested in double transgenic mice created by crossing the Acan‐CreER‐Ires‐Luc line with a Rosa26‐lacZ reporter mouse. The expression pattern of the transgene of our line was restricted to cartilage from embryonic to adult stages. β‐galactosidase staining was observed in growth plate, articular cartilage, as well as fibrocartilage of meniscus, trachea, and intervertebral discs. Similar staining was observed in a previously described Agc1 tm(IRES‐creERT2) murine line. The presence of luciferase in our transgene allows the visualization of the transgene expression in live animals. Weekly measurements from 2 to 8 weeks of age showed a reduction in luminescence in knee joints between 2 and 4 weeks of age, but stabilization thereafter. Following the surgical induction of osteoarthritis at 12 weeks of age, the level of luminescence remained the same in the knee joints for 8 weeks. This Acan‐CreER‐Ires‐Luc murine line allows indirect monitoring of the transcriptional activity of the Acan gene via expression of luciferase, while the inducible Cre recombinase activity facilitates studies involving gain or loss of gene expression in cartilage. genesis 1–10. © 2013 Wiley Periodicals, Inc.